Being in the world : dialogue and cosmopolis - Dallmayr, Fred R. (Fred Reinhard), 1928- (Lexington, KY : University Press of Kentucky, 2013)
It is commonly agreed that this is the era of globalization, but the profound consequences of this development are rarely understood. Usually, globalization is equated with the expansion of economic and financial markets and the proliferation of global networks of communication. In truth, much more is at stake: traditional concepts of individual and national identity, as well as perceived relationships between the self and others, are undergoing profound change. Every town has become a potential cosmopolis - an international city - affecting the way that people conceptualize the relationship between public order and political practice. In this book, a political theorist explores the globe's transition from the traditional Westphalian system of states to an interlocking cosmopolitan network.
Introduction -- Being in the World : A Moving Feast -- Cosmopolitanism : In Search of Cosmos -- After Babel : Journeying toward Cosmopolis -- Humanizing Humanity : Education for World Citizenship -- Ethics and International Politics : A Response -- Befriending the Stranger : Beyond the Global Politics of Fear -- The Body Politic : Fortunes and Misfortunes of a Concept -- A Secular Age? : Reflections on Taylor and Panikkar -- Post-Secularity and (Global) Politics : A Need for Radical Redefinition -- Political Self-Rule : Gandhi and the Future of Democracy -- Radical Changes in the Muslim World : Whither Democracy? -- Opening the Doors of Interpretation : In Memory of Nasr Abu Zayd and Mohammed al-Jabri -– Appendix A : Beyond Multiculturalism? : For Bhikhu Parekh –- Appendix B : Cosmopolitan Confucianism? : Chinese Traditions and Dialogue -- Appendix C : The Complexity of Difference : Comments on Zhang Longxi -– Appendix D : Dialogue in Practice : Conversation with Members of a "Youth Forum".
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Cosmopolitanism -- Philosophy; Globalization -- Philosophy; Political science -- Philosophy; Cosmopolitisme -- Philosophie; Mondialisation -- Philosophie; POLITICAL SCIENCE -- Globalization; PHILOSOPHY -- Political; Political science -- Philosophy; Globalization -- Philosophy; Cosmopolitanism; Globalization; Electronic books